Metalinguistic knowledge and correct use of accent mark - Mamani, Luis (2013)
Spelling success supposes the proper use of specific information. Non-experts orthographic correctors lack this information or they do have deficiencies, when using it. Overcoming this condition seems simple: the experts must pass on this knowledge by telling the novice what information to use and how. However, there is a greater challenge: experts do not know exactly what information they handle and how they use it. So it is crucial to identify these skills and how they are used. That is the purpose of this contribution. In this endeavor we have used techniques like the elicitation of information, from the cognitive task analysis. Results show that a properly use of the orthographic accent requires a proper management of a set of metalinguistic knowledge among which we can mention the differentiation of kinds of words, the determination of the number of syllables, the identification of a specific type of hiatus, among others. These findings might have implications when teaching written orthographic accent.